PENGGUNAAN CAMPURAN CASSAVA DAN TEPUNG INDIGOFERA SEBAGAI PENGGANTI JAGUNG DALAM RANSUM TERHADAP PERFORMANS PUYUH PETELUR PADA UMUR 1 – 5 MINGGU - Johan Setianto; Edi Soetrisno; Suharyanto Suharyanto; Tamzan Tamzan (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2005)
The study was conducted to investigate the effects of cassava and indigofera leaf meals as corn’s substitution on 1 – 5 weeks old quail’s performance. Two hundred and forty of 1 week-old quail were used in the study. Experiment consisted of six treatment groups with eight pen replicates of five quails allocated randomly to each dietary treatment. One group was the control with no substitution while it contains cassava only as corn’s substitution completely and other groups were given cassava and 2.5% indigofera leaf meal as corn’s substitution, cassava and 5% indigofera leaf meal as corn’s substitution, cassava and 7.5% indigofera leaf meal as corn’s substitution and, cassava and 10% indigofera leaf meal as corn’s substituion. The ration used was isoprotein (24%) and isoenergy (2900 kcal kg-1). The result of this study was no significant among treatments (P>0.05) for feed intake. The body weight and body weight gain were significant (P<0.05) where the higher indigofera leaf level the lower body weight and body weight gain. The low body weight gain appropriates best state for layer quail. The ration conversion was significant (P<0.05) where the higher indigofera leaf meal level the higher ration conversion value and it indicates dreadful condition. It is suggested to evaluate the effects on layer period.